Physical properties of single-wall carbon nanotubes in cell culture and their dispersal due to alveolar epithelial cell response. (October 2013) - Fujita, Katsuhide; Fukuda, Makiko; Endoh, Shigehisa; Kato, Haruhisa; Maru, Junko; Nakamura, Ayako; Uchino, Kanako; Shinohara, Naohide; Obara, Sawae; Nagano, Reiko; Horie, Masanori; Kinugasa, Shinichi; et al.
Abstract Concern over the influence of carbon nanotubes (CNTs) on human health has arisen due to advances; however, little is known about the potential toxicity of CNTs. In this study, impurity-free single-wall carbon nanotubes (SWCNTs), with different physical properties in cell culture medium, were prepared by a novel dispersion procedure. SWCNTs with small bundles (short linear shape) and SWCNTs with large bundles (long linear shape) did not cause a significant inhibition of cell proliferation, induction of apoptosis or arrest of cell cycle progression in A549 alveolar epithelial cells. Expression of many genes involved in the inflammatory response, apoptosis, response to oxidative stress and degradation of the extracellular matrix were not markedly upregulated or downregulated. However, SWCNTs with relatively large bundles significantly increased the level of intracellular reactive oxygen species (ROS) in a dose-dependent manner, and the levels of these ROS were higher than those of SWCNTs with relatively small bundles or commercial SWCNTs with residual metals. Transmission electron microscopy (TEM) revealed that impurity-free SWCNTs were observed in the cytoplasm and vacuoles of cells after 24 h. These results suggested that the physical properties, especially the size and length of the bundles of the SWCNTs dispersed in cell culture medium, contributed to a change in intracellular ROS generation, even for the same bulk SWCNTs. Additionally, the residual metals associated with the manufacturing of SWCNTs may not be a definitive parameter for intracellular ROS generation in A549 cells.